Popcorn‐Shaped Magnetic Core–Plasmonic Shell Multifunctional Nanoparticles for the Targeted Magnetic Separation and Enrichment, Label‐Free SERS Imaging, and Photothermal Destruction of Multidrug‐Resistant Bacteria. Issue 8 (7th January 2013) - Fan, Zhen; Senapati, Dulal; Khan, Sadia Afrin; Singh, Anant Kumar; Hamme, Ashton; Yust, Brian; Sardar, Dhiraj; Ray, Paresh Chandra
Abstract Over the last few years, one of the most important and complex problems facing our society is treating infectious diseases caused by multidrug‐resistant bacteria (MDRB), by using current market‐existing antibiotics. Driven by this need, we report for the first time the development of the multifunctional popcorn‐shaped iron magnetic core–gold plasmonic shell nanotechnology‐driven approach for targeted magnetic separation and enrichment, label‐free surface‐enhanced Raman spectroscopy (SERS) detection, and the selective photothermal destruction of MDR Salmonella DT104. Due to the presence of the "lightning‐rod effect", the core–shell popcorn‐shaped gold‐nanoparticle tips provided a huge field of SERS enhancement. The experimental data show that the M3038 antibody‐conjugated nanoparticles can be used for targeted separation and SERS imaging of MDR Salmonella DT104. A targeted photothermal‐lysis experiment, by using 670 nm light at 1.5 W cm−2 for 10 min, results in selective and irreparable cellular‐damage to MDR Salmonella. We discuss the possible mechanism and operating principle for the targeted separation, label‐free SERS imaging, and photothermal destruction of MDRB by using the popcorn‐shaped magnetic/plasmonic nanotechnology.